2006
DOI: 10.1016/j.febslet.2006.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide synthesis and degradation in isolated rat liver peroxisomes

Abstract: Analyzing peroxisomal phosphoinositide (PId # ) synthesis in highly purified rat liver peroxisomes we found synthesis of phosphatidylinositol 4-phosphate (PtdIns4P), PtdIns(4,5)P 2 and PtdIns(3,5)P 2 . PtdIns3P was hardly detected in vitro, however, was observed in vivo after [ 32 P]-phosphate labeling of primary rat hepatocytes. In comparison with other subcellular organelles peroxisomes revealed a unique PId pattern suggesting peroxisomal specificity of the observed synthesis. Use of phosphatase inhibitors e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Syt7-C2AB mainly bound PI(4,5)P 2 and to a much lesser extent PI(5)P and PS; no signal was observed for other phospholipids ( Figure 5A). It has been reported that peroxisome can synthesize significant amounts of PIP2 including PI(4,5)P 2 (Jeynov et al, 2006). To further validate Syt7-PI(4,5)P 2 interaction under a more relevant format, we performed the liposome flotation assay using liposomes mimicking phospholipid composition of the mammalian peroxisome membrane (PC:PE:PI:PS = 54:36:5:5) (Hardeman et al, 1990).…”
Section: Synaptotagmin VII Is a Lysosomal Protein Binding Peroxisomementioning
confidence: 99%
“…Syt7-C2AB mainly bound PI(4,5)P 2 and to a much lesser extent PI(5)P and PS; no signal was observed for other phospholipids ( Figure 5A). It has been reported that peroxisome can synthesize significant amounts of PIP2 including PI(4,5)P 2 (Jeynov et al, 2006). To further validate Syt7-PI(4,5)P 2 interaction under a more relevant format, we performed the liposome flotation assay using liposomes mimicking phospholipid composition of the mammalian peroxisome membrane (PC:PE:PI:PS = 54:36:5:5) (Hardeman et al, 1990).…”
Section: Synaptotagmin VII Is a Lysosomal Protein Binding Peroxisomementioning
confidence: 99%
“…3H and I) and pex14p (not shown) [44], [45]. Peroxisomes have a unique PtdInsPs system [46], but there is no established treatment for modulating their PtdInsPs levels. The treatments we attempted, wortmannin and LY294002, affecting PtdIns3P levels, and ionomycin, reducing PtdIns(4,5)P2 levels, did not alter the peroxisomal enrichments of the fluorescent proteins.…”
Section: Resultsmentioning
confidence: 99%
“…By phosphorylation of the myosin-binding subunit of myosin phosphatase and/or the myosin light chain of myosin II, ROCKII enhances myosin ATPase activity [47], [48]. Moreover, ROCKII contains a well-defined pleckstrin homology domain binding to PtdIns(4,5)P 2 the synthesis of which in the peroxisomal membrane was recently reported [49].…”
Section: Discussionmentioning
confidence: 97%